2021
DOI: 10.1021/acsami.0c21412
|View full text |Cite
|
Sign up to set email alerts
|

Stable Cycle Performance of a Phosphorus Negative Electrode in Lithium-Ion Batteries Derived from Ionic Liquid Electrolytes

Abstract: Although high-capacity negative electrode materials are seen as a propitious strategy for improving lithium-ion battery (LIB) performance, their advancement is curbed by issues such as pulverization during charge-discharge and the formation of unstable solid electrolyte interphase (SEI). In particular, electrolytes play a vital role to determine the properties of SEI layer. Thus, in this study, we investigate the performance of a red phosphorus/acetylene black composite (P/AB) prepared by high energy ball-mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…It is worth noting that the amount of S- and N-based components is considered to be one of the key differentiators between SEI layers formed by organic electrolytes (e.g., Li­[PF 6 ]-EC/DMC) and IL electrolytes (e.g., Li­[FSA]-[C 2 C 1 im]­[FSA]). In fact, previous studies on NIBs and LIBs utilizing [FSA] − -based electrolytes have identified the abundance of sulfur-based components in the SEI layer as the main factor behind their improved electrochemical performance in ILs …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the amount of S- and N-based components is considered to be one of the key differentiators between SEI layers formed by organic electrolytes (e.g., Li­[PF 6 ]-EC/DMC) and IL electrolytes (e.g., Li­[FSA]-[C 2 C 1 im]­[FSA]). In fact, previous studies on NIBs and LIBs utilizing [FSA] − -based electrolytes have identified the abundance of sulfur-based components in the SEI layer as the main factor behind their improved electrochemical performance in ILs …”
Section: Resultsmentioning
confidence: 99%
“…In fact, previous studies on NIBs and LIBs utilizing [FSA] − -based electrolytes have identified the abundance of sulfur-based components in the SEI layer as the main factor behind their improved electrochemical performance in ILs. 70…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Not only that, the size of the SEI itself will also affect its own stability. For example, when Bian et al studied tea polyphenols (TP) as a new reactive electrolyte additive applied to lithium-ion batteries, they found that the additive TP can remove ethylene carbonate and form a stable polymer. It is concluded that the thickness of the SEI film will affect its own stability, and the additive TP can react with unstable free radicals to form a polymer, which greatly improves the stability of the SEI film.…”
Section: Production and Impacted Factor Of Seimentioning
confidence: 99%
“…Strong covalent bonds form within single layers, in between which it is van der Waals force [37][38][39][40][41][42][43]. With this unique lattice structure, black phosphorus shows better stability than its allotropes (white and red phosphorus), and it also has high carrier mobility, anisotropic in-plane properties and specific capacity [21,[44][45][46], which makes it ideal as negative electrode material for lithium and sodium batteries [30,[47][48][49][50][51][52][53], as well as photocatalysts. With construction [54][55][56][57][58], doping [59][60][61][62][63][64], or heterojunctions [65][66][67][68][69][70][71], the stability, charge transport, and catalytic performance of black phosphorus can be further improved.…”
Section: Introductionmentioning
confidence: 99%